Spiritualitas Salat Mahasiswa dalam Perspektif Imam Al-Ghazali - Ajrina, Naela Ni'matu; Nurlailatul Musyafaah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This article discusses the implementation of prayer as a spiritual value in society by taking the perspective of Imam Al-Ghazali as a famous Islamic and Sufi philosopher until today. This study focuses on society in the implementation of prayer which of course is in the midst of their busy lives or demands of different circumstances. In essence, prayer is a communication between a servant and his God, so there is a way for a servant to enjoy the opportunity. However, this is not easy and even many of us cannot enjoy this communication. Starting from here, we take Imam Al-Ghazali's thoughts in providing a different view of the meaning of prayer. So that this can be used as a benchmark for not underestimating a worship, especially prayer. Because prayer is a pillar of religion and worship that is first accounted for on the Day of Judgment. This study uses a qualitative method with a philosophical approach, which is a method used in this study. By distributing questionnaires and will be strengthened by the results of interviews with several respondents. So that we can find out the results of the research that will be carried out effectively and actually.